ISLAM DAN KEBANGSAAN: UPAYA MENEGUHKAN KEMBALI KEBANGSAAN DALAM DIRI SEBAGIAN MAHASISWA ISLAM DI INDONESIA - Ahmad Shunhaji; Khasnah Syaidah; Asep Eka Mulyanudin (STIT AL-AMIN KREO TANGERANG, 2022)
Nationalism doesn’t seem to be firmly entrenched in some Islamic students in Indonesia or may disappear altogether, this can be concluded from various news reports that show that radicalism has entered the scope of their lives. This study was made with the aim of exploring how the national values in the Qur'an and al-Hadith, as well as the national values exemplified by Islamic figures in Indonesia in the context of establishing the Unitary State of the Republic of Indonesia, were made. This research was conducted by using the literature study method in extracting data, and using content analysis in analyzing the data. The results of this research indicate that nationality has a strong foundation in the Qur'an and al-Hadith, and has also been practiced in the process of establishing the Unitary State of the Republic of Indonesia, by Islamic figures in Indonesia. So it can be concluded that the anti-national attitude which is believed even spread by some Islamic students in Indonesia, is an act that cannot be justified even very detrimental, so that it can damage the integrity of the Unitary State of the Republic of Indonesia